Analysis of Cosmetic Products Without Indonesian Language Labels in Sungai Penuh City: A Review of Islamic Law on Business Actors' Compliance with Government Regulations - M. Ibrahim Aziz; Repelita Repelita; Defril Hidayat; Ari Bakti Windi Aji (Al Irsyad: Jurnal Studi Islam, 2026)
The continued circulation of cosmetic products without Indonesian-language labels in Sungai Penuh City indicates the low compliance of business actors with government regulations. This study aims to analyze cosmetic products without Indonesian-language labels, based on positive and Islamic law, regarding business actors’ compliance in Sungai Penuh. This qualitative case study research employed observation, interviews, and documentation involving cosmetic business actors in Sungai Penuh City. The data were analyzed descriptively in accordance with positive and Islamic law. The results show that imported cosmetics without Indonesian-language labels are still being traded in several cosmetic stores in Sungai Penuh City. Business actors generally understand only requirements related to BPOM approval, mercury-free products, and halal labels, but have not yet fully understood the obligation to provide Indonesian-language labels as regulated by Law Number 8 of 1999. From the perspective of Islamic law, such practices do not yet reflect the principles of honesty (?idq), transparency of information (bayan), public benefit (ma?la?ah), and the protection of consumer rights. Low compliance is driven by limited government socialization and suboptimal supervision, necessitating continuous improvement in education and regulatory enforcement across all business actors. The conclusion of this study is that business actors’ compliance with product labeling requirements remains low and has not fully complied with the provisions of positive law or Islamic law principles. The significance of this research lies in strengthening the study of positive and Islamic law to improve compliance with labeling requirements and consumer protection for cosmetic products in Indonesia.